Structure et biogéographie des communautés de pico- et de nanoeurcaryotes pélagiques autour de l'archipel du Svalbard - Carrier, Vincent (Université Laval, 2016)
The Arctic is warming rapidly and there is an urgent need to anticipate the effect this will have on the microbial eukaryotes at the base of the food chain. Arctic Ocean phytoplankton include pico- and nano-eukaryotes (0.45-10 μm cell size), many of these are unique ecotypes found only in the Arctic, but others are advected in from lower latitude oceans. As temperate oceans waters penetrate further into the Arctic, knowledge of whether microbial communities could be displaced is needed. Svalbard is an ideal region to address questions on microbial communities under the influence of polar and temperate processes. Although geographically close, the fjords and offshore regions surrounding Svalbard are subjected to alternate intrusions of Atlantic and Arctic waters in addition to local conditions. Eight sites were surveyed in July 2013 with the aim of identifying microbial eukaryotes at a range of depths and water masses around Svalbard. In addition to standard oceanographic variables, seawater was collected for targeted amplicon libraries based on the 18S SSU rRNA gene and rRNA using high throughput amplicon sequencing. Five of the sites had low chlorophyll concentrations with typical post bloom summer communities; dinoflagellates, ciliates, putative alveolate parasites, chlorophytes and prymnesiophytes. Intrusive water masses and local environmental conditions correlated to community structure, with the origin of the water mass contributing most to the phylogenetic distance of the microbial communities. In three of the fjords, chlorophyll concentrations were high, consistent with a bloom. One fjord was dominated by Phaeocystis, a second by a putative Arctic clade of Pelagophyceae, and the third by mixed species. Overall, a strong signal of Arctic ecotypes prevailed around Svalbard. L’Arctique s’est réchauffé rapidement et il y a urgence d’anticiper les effets que cela pourrait avoir sur les protistes à la base de la chaîne alimentaire. Le phytoplancton de l’Océan Arctique inclut les pico- et nano-eucaryotes ...